2016
DOI: 10.2196/resprot.4865
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of a Web-Based Weight Loss Intervention for Low-Income Women of Reproductive Age: A Pilot Study

Abstract: BackgroundLow-income women of reproductive age are at increased risk for obesity and resulting increases in the risk of maternal/fetal complications and mortality and morbidity. Very few weight-loss interventions, however, have been targeted to this high-risk group. Based on the high prevalence of social media use among young and low-income individuals and previous successes using group formats for weight-loss interventions, the use of social media as a platform for weight-loss intervention delivery may benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(106 citation statements)
references
References 20 publications
5
97
1
1
Order By: Relevance
“…The majority of intervention studies targeted adult populations (26/34, 76%) [ 18 , 41 - 44 , 48 , 50 , 52 , 54 - 56 , 58 - 60 , 66 , 72 , 75 , 77 , 79 , 82 - 84 , 87 , 88 , 92 , 93 ]. Among them, specific populations of users were adult women [ 18 , 50 , 66 , 84 , 88 ], young adults aged 18-35 years [ 55 , 56 , 72 ], pregnant adult women [ 79 , 92 ], and collegiate athletes [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of intervention studies targeted adult populations (26/34, 76%) [ 18 , 41 - 44 , 48 , 50 , 52 , 54 - 56 , 58 - 60 , 66 , 72 , 75 , 77 , 79 , 82 - 84 , 87 , 88 , 92 , 93 ]. Among them, specific populations of users were adult women [ 18 , 50 , 66 , 84 , 88 ], young adults aged 18-35 years [ 55 , 56 , 72 ], pregnant adult women [ 79 , 92 ], and collegiate athletes [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intervention studies covered a limited range of health conditions, with most users of social media being overweight and obese (15/34, 44%) [ 41 , 44 , 52 , 54 - 56 , 59 , 60 , 72 , 75 , 82 - 84 , 88 , 92 ] or obese (3/34, 9%) [ 63 , 87 , 93 ]. In total, 8 intervention studies targeted healthy users (8/34, 24%) [ 18 , 43 , 50 , 58 , 66 , 76 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, four pilot, randomized, controlled, lifestyle behavioral intervention studies that targeted low‐income young women with overweight or obesity were conducted to help these women lose weight mainly via promotion of healthy eating . Unlike MIM, these four pilot studies only assessed measurements immediately after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the four prior studies are not consistent with results of the present study, which revealed that intervention participants were more confident, had better emotional coping responses, received more social support, and ate significantly less dietary fat and fast food than the comparison participants immediately after the 16‐week intervention. Cavallo et al used in‐person group sessions and Web‐based modalities including social media to deliver the intervention. They did not find any significant difference between the intervention and control groups in fruit and vegetable intake immediately after the 20‐week intervention .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation